2015
DOI: 10.1177/1077801215618806
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Batterer Intervention and Prevention Program With Alternative Court Dispositions on 12-Month Recidivism

Abstract: Studies of batterer intervention and prevention programs (BIPPs) offer mixed results regarding their effect on recidivism. The purpose of this study was to examine the effectiveness of BIPP for cases assigned to a misdemeanor family court. This study focused on determining whether BIPP cases, compared with alternative sanctions, had significantly lower recidivism rates 12 months after program involvement. Findings indicated that BIPP was more effective than jail or regular dismissal in reducing the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Chen, Bersani, Myers, and Denton (1989) found that only those defendants who attended 75% or more of the treatment sessions had decreased recidivism. Boots, Wareham, Bartula, and Canas (2016) indicated that the BIP was more effective than jail or regular dismissal in reducing the likelihood of future arrests, but not more effective than plea-deferred adjudication and conditional dismissal. The remaining seven studies (41.2%) did not find a significant difference in subsequent IPV perpetration between the BIP and no-treatment groups.…”
Section: Overviewmentioning
confidence: 99%
“…Chen, Bersani, Myers, and Denton (1989) found that only those defendants who attended 75% or more of the treatment sessions had decreased recidivism. Boots, Wareham, Bartula, and Canas (2016) indicated that the BIP was more effective than jail or regular dismissal in reducing the likelihood of future arrests, but not more effective than plea-deferred adjudication and conditional dismissal. The remaining seven studies (41.2%) did not find a significant difference in subsequent IPV perpetration between the BIP and no-treatment groups.…”
Section: Overviewmentioning
confidence: 99%
“…Similar to other types of problem-solving courts (Boots, Wareham, Bartula, & Canas, 2016; Gover, Brank, & MacDonald, 2007), the SWIFT Court judge uses motivational interviewing to attempt to determine the underlying reasons for violations, regardless of the severity, and orders participants to corresponding programming multiple times throughout their supervision term. Moreover, the judge who oversees SWIFT Court is a former prosecutor with a reputation for being very tough; however, she believes in providing offenders every opportunity to change.…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be lively debate within the field regarding the efficacy of intensive supervision programs, as scholarship indicates that these programs frequently result in more technical revisions, higher costs, and more recidivism (see Hyatt & Barnes, 2017) that may result in “backdoor sentencing” (see Medina, 2017). With the rise of such problem-solving courts such as HOPE that target various subpopulations of offenders, rigorous evaluations that explore the efficacy of programming for challenging correctional populations are an important charge for scholars in helping practitioners direct scarce community resources (Boots et al, 2016; Mitchell, Wilson, Eggers, & MacKenzie, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Like compliance monitoring, another key programming component for DVCs is their collaborative relationship with community DV offender treatment agencies and non-profits, typically referred to as Batterer Intervention and Prevention Programs (BIPPs). Ideally, a BIPP case manager or BIPP group facilitator participates in processing DVC hearings as a vital stakeholder, sending regular updates concerning forward progress to completion of the program as part of the accountability of the offender with the judge (Boots et al, 2016).…”
Section: Offender Management and Treatmentmentioning
confidence: 99%